Impairing fluoride export of Aspergillus fumigatus mitigates its voriconazole resistance - Binder, Jasmin; Held, Jürgen; Krappmann, Sven (International Journal of Antimicrobial Agents, 2019)
Fungi have evolved specific export activities to balance intracellular levels of the toxic ion fluoride, while the first-line antimycotic voriconazole contains fluorine. This study aimed to explore whether impaired fluoride export might result in altered susceptibilities of the human pathogenic mould Aspergillus fumigatus towards this antifungal compound. Functional characterization of the putative fluoride exporter in A. fumigatus was performed in the context of azole resistance by generating deletion strains that were assessed for their resistance against fluoride and voriconazole. The FexA fluoride exporter of A. fumigatus appears to be expressed constitutively, and targeting its encoding gene results in significantly increased sensitivity towards this halide. Impaired fluoride export correlates with increased susceptibility of an azole-resistant fexAΔ strain. These results demonstrate that the fexA-encoded gene product is the major fluoride export activity of A. fumigatus, and that voriconazole serves as a source of fluoride. However, these data do not support the application of voriconazole based on fluoride toxicity.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Aspergillosis; Azole resistance; FEX